Automated Cultivation System for Microalgae: Growth Factors and Control - Khor, Jiun G.; Lim, Hooi Ren; Chia, Wen Yi; Chew, Kit Wayne (Current Nutrition & Food Science, 2022)
Background: Microalgae have been a hot research topic due to their various biorefinery applications, particularly microalgae as potential alternative nutraceuticals and supplements have a large and rapidly growing market. However, commercial production is limited due to high processing cost, low efficiency, and scale up of biomass production. Objective: It is important to control the microalgae cultivation system with optimal parameters to maximize biomass productivity. The growth factors, including pH, temperature, light intensity, salinity, and nutrients, are discussed as these can significantly affect the cultivation. To monitor and control these in real-time, an automated system incorporating advanced digital technologies like sensors, controllers, artificial intelligence (AI), and the Internet of Things (IoT) could be applied. Conclusion: This perspective provides insights into the implementation of an automated microalgae cultivation system that improves productivity, effectiveness, and efficiency.
Keywords: temperature